Political Influence on the Constitutional Court in the Republic of Macedonia: Reflections through the Dissenting Opinions in the Period of 2012-2015 - Sonja Stojadinovic (Constitutional Review, 2019)
The demo Christian political party VMRO-DPMNE had a long period of ruling of the Republic of Macedonia, (2006-2016). During that period many cases of political pressure on the state institutions have occurred. The Constitutional Court wasn’t an excepted of that political pressure. Starting from the process of appointment of new judges, through the shocking decisions upon official citizens’ complaints and human rights appeals, to a complete reflection of the political interference and pressure through the dissenting opinions written and published by some constitutional judges. The former government has used all the tools, legal and non-legal, to put under control the Constitutional Court. If we put aside the political interference into the appointment of new and incompetent judges, one of the most used tools as a form of resistance was the dissenting opinion. This legal tool is present in the Book of Rules of the Constitutional Court of the Republic of Macedonia, but also in the legal systems in the Eastern Europe, Germany, Spain, Greece and all other states whose legal systems are created by the German legal system. It gives space and chance for one or several constitutional judges to express disagreement upon a decision brought by the majority in the court. This tool was frequently used by several judges from the Constitutional Court in the Republic Macedonia in the given period through which we can see strong political influence on their work. Therefore, the research questions are as follows: What were the “models” of political influence that were used on the Constitutional Court during the period of 2012-2015? How were they used and what are the dissenting opinions reflecting? To answer the said questions, the model of qualitative research will be used together with several dissenting opinions as case studies. The aim of this approach is to explain the different aspects of political influence on the work of the Constitutional Court within the given period. The findings of this research can be used for further development of the interest for researching of the work and role of the Constitutional Court in the Republic of Macedonia.